Nano - maxillofacial surgery: development which cannot be avoided - P.T., Abhishek; Pethkar, Radhika; Nizar, Sarin; Dalvi, Neethi (International Journal of Dental Research, 2017)
Objective:1)Â Â Â Â Â To understand the importance of nanotechnology in maxillofacial surgery.2)Â Â Â Â Â To impress the importance of adaptingnanotechnology in making the surgeries and diagnosis easy and more effective.Design: Various databases, including MEDLINE and EMBASE, were searchedto identify published articles related to nanotechnology and dentistry as well as in maxillofacial surgery. An exhaustive search was conducted and four reviewers independently completed inclusion assessment, data extraction, and risk of bias assessment for all studies identified.Conclusion: The review foundlittle evidence ofany recent research papers conducted aboutnanotechnology in dentistry or maxillofacial surgery. However , our study stress upon the need ofthe health care professionals like dental surgeons, specially oral and maxillofacial surgeons to be aware of the importance ofadapting new trends in nanotechnology.Maxillofacial surgeons need to takemore efforts and the supporting associations or societies need to provide more resources in the field of research to help the oral and maxillofacial surgeons be at par with the advanced world of nanotechnology and nanosurgery.